The Influence of Export, Import and Population Values on The Gross Domestik Product of ASEAN Countries Period 2000-2009 - Zikriatul Ulya (el-Jizya: Jurnal Ekonomi Islam, 2022)
This study aims to determine the effect of exports, imports and population on the Gross Domestic Product (GDP) of case studies in Indonesia, Malaysia, Singapore, Brunei Darussalam and the Philippines in 2000-2019. This type of research uses quantitative descriptive methods with panel data regression analysis, as well as data collection with documentation techniques, namely the data obtained from word bank data. The results show that exports have a positive and significant effect on gross domestic product with the regression coefficient value on the export variable amounting to 0.589385, which means that every 1% increase in exports will increase GDP by 58.94%, imports have positive and no significant effect on products. Gross domestic product with a regression coefficient value on the import variable is 0.0283 which means that every 1% increase in imports will increase GDP by 2.83%, the population has a positive and significant effect on gross domestic product with the regression coefficient value on the population variable is 14,653 which This means that if there is an increase in the population of 1%, it will increase the gross domestic product by 14.65%, then simultaneously exports, imports and the population will positively and significantly increase the Gross Domestic Product (GDP) with a coefficient value of 0.9693 which means that meaning that the variables of exports, imports and population are able to explain the variable gross domestic product (GDP) of 96.90% while the remaining 3.10% is explained by other variables not mentioned in this study.